MARKET REACTION TO MERGER ANNOUNCEMENT: EMPIRICAL STUDY ON THE COMPANIES LISTED ON IDX (INDONESIA STOCK EXCHANGE) - B11111044, BETI SEPLIANTINI (Jurnal Manajemen Update, 2015)
The aim of the research  was to reveal  the reaction of the  stock  market on the company to merger announcements.  It was an empirical study  on  the companies  listed  on IDX(Indonesia Stock Exchange) in the  period 2004-2014 by looking at  the  abnormal return around the time of the  announcement, comparing the average abnormal return and  the average trading  volume activity  before and after the merger.  This was a  comparative research  a case study. It was also  an event study. The population in this study included39 companies that announced merger in the  period  of  2004-2014 with a total sample of 30 companies  selected through  a  purposive sampling technique.  The period  of the research was 21 days, 10 days before and 10 days after the announcement.The results of the research  showed that the probability value or significance value of AR, AAR and TVA  was greater  that the  significance level used.  The abnorrnal return around the  time of the  announcement  was  not significant either before the announcement t-10  until  t-1 or  after the announcement t+1  until  to t+10, and at the time of the announcement t+0.  The average abnormal return (AAR)  10 days before and 10 days after the announcement  was  0.899>0.05  meaninng  there was  no significant difference before and after the merger  announcement. The average TVA 10 before and 10 days after the announcement was  0.600>0.05  so there was  no significant difference. It can be concluded that the average AR and the average TVA before and after the announcement of the merger indicated that there was no significant difference.Keywords:  Merger Announcement, Event Study,  Abnormal Return, Trading Volume Activity.